2022
DOI: 10.1177/23259671221077933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Opioid Use on Patients Undergoing Hip Arthroscopy

Abstract: Background: Opioids are commonly used to treat postoperative pain; however, guidelines vary regarding safe opioid use after hip arthroscopy. Purpose/Hypothesis: The purposes were to (1) identify risk factors for persistent opioid use, (2) assess the effect of opioid use on outcomes, and (3) describe common opioid prescribing patterns after hip arthroscopy. It was hypothesized that preoperative opioid use would affect complication rates and result in greater postoperative opioid use. Study Design: Case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…This analysis is similar to other literature which has shown that preoperative opioid use is a risk factor for prolonged opioid use following hip arthroscopy [2,5,11,23,28,33]. Similar patterns have been observed in various other orthopaedic surgeries, including anterior cruciate ligament reconstruction (ACLR) [3], total joint arthroplasty [27,43] and orthopaedic trauma [27], further highlighting the broader relevance of this risk factor for postoperative opioid use.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This analysis is similar to other literature which has shown that preoperative opioid use is a risk factor for prolonged opioid use following hip arthroscopy [2,5,11,23,28,33]. Similar patterns have been observed in various other orthopaedic surgeries, including anterior cruciate ligament reconstruction (ACLR) [3], total joint arthroplasty [27,43] and orthopaedic trauma [27], further highlighting the broader relevance of this risk factor for postoperative opioid use.…”
Section: Discussionsupporting
confidence: 87%
“…While female sex has been demonstrated to be a possible risk factor for inferior clinical outcomes following hip arthroscopy [18], it is unclear if female sex is a risk factor for prolonged postoperative opioid use [2, 11, 33]. This finding is consistent with some literature pertaining to ACLR [3, 31], arthroplasty [43] and trauma [27] but is likely multifactorial and of importance for ongoing research.…”
Section: Discussionsupporting
confidence: 71%
“…Kunkel et al 23 found a 5-fold and 4-fold increase in the percentage of patients with chronic opioid use following THA and total knee arthroplasty (TKA), respectively. Rogers et al 24 analyzed hip arthroscopy patients, finding that those who used opioids before the procedure needed more refills following the procedure. Also, patients with a formal opioid use disorder diagnosis had significantly greater risk for revision hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Similar high-level studies have been performed with respect to anterior cruciate ligament reconstruction (ACLR), 15 , 20 , 41 meniscal procedures, 30 , 46 and hip arthroscopy. 9 , 28 However, a survey of the American Academy of Orthopaedic Surgeons (AAOS) attendees highlighted many inconsistencies, and often excess, in opioid prescription patterns after common procedures, 35 and reliable, evidence-based opioid prescription recommendations after various arthroscopic procedures are sparse. 27 , 30 The purpose of this study was to both quantify the amount of opioid prescription used after common sports medicine surgeries (meniscectomy, meniscal repair, ACLR with various graft selections, and hip and shoulder arthroscopy with labral repair) and further understand the allocation of opioid pain medications that go unused.…”
mentioning
confidence: 99%